KARAKTERISASI PENYEDAP RASA ALAMI BERBASIS TEMPE DAN JAMUR TIRAM - Zulfaa, Ulayyaa; Minah, Faidliyah Nilna (jurnal ATMOSPHERE, 2025)
Tempeh as a fermented soybean product has high nutritional value and has become an important part of local culinary in Malang. Oyster mushroom (Pleurotus ostreatus) cultivation is also growing rapidly in Malang due to the supportive natural conditions and promising economic potential. The advantages of these two raw materials make them very potential to be developed into innovative food products, one of which is natural flavoring. This study aims to develop natural flavorings based on tempeh and oyster mushrooms as a healthier substitute for MSG. Variations in the proportion of tempeh and oyster mushrooms and drying temperatures (70°C, 65°C, 60°C, 55°C) were tested to analyze product characteristics. The parameters tested included water content, carbohydrates, protein, and sensory tests. The results of the study are expected to provide an alternative natural flavoring that is safe and highly nutritious.